2010
DOI: 10.1146/annurev-genet-102209-163602
|View full text |Cite
|
Sign up to set email alerts
|

The RecQ DNA Helicases in DNA Repair

Abstract: The RecQ helicases are conserved from bacteria to humans and play a critical role in genome stability. In humans, loss of RecQ gene function is associated with cancer predisposition and/or premature aging. Recent data have shown that the RecQ helicases function during two distinct steps during DNA repair; DNA end resection and resolution of double Holliday junctions (dHJs). RecQ functions in these different processing steps has important implications for its role in repair of double-strand breaks (DSBs) that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
312
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(315 citation statements)
references
References 172 publications
(243 reference statements)
1
312
0
2
Order By: Relevance
“…However, it remains a matter of debate which DNA helicase mediates DNA2-catalyzed resection in mammalian cells. Mammals pos-sess five RecQ homologues: RECQ1, BLM, WRN, RECQ4, and RECQ5 (20). Biochemical studies have shown that human DNA2 can act in conjunction with the BLM helicase and RPA to mediate 5Ј-3Ј resection of DNA ends in vitro (17).…”
mentioning
confidence: 99%
“…However, it remains a matter of debate which DNA helicase mediates DNA2-catalyzed resection in mammalian cells. Mammals pos-sess five RecQ homologues: RECQ1, BLM, WRN, RECQ4, and RECQ5 (20). Biochemical studies have shown that human DNA2 can act in conjunction with the BLM helicase and RPA to mediate 5Ј-3Ј resection of DNA ends in vitro (17).…”
mentioning
confidence: 99%
“…These enzymes are involved in DNA replication, recombination, repair, and chromosome segregation, and their malfunctioning may cause genome instability, premature aging, infertility, and cancer (for recent reviews, see Refs. [1][2][3][4][5]. At the biochemical level, RecQ-Top3 enzymes induce coordinate DNA topoisomerase, ATPase, DNA unwinding, and DNA annealing and act on particular DNA structures to modify their topological linkages.…”
mentioning
confidence: 99%
“…There is conservation of RecQ proteins from bacteria to humans. Whereas bacteria have one RecQ helicase, humans have evolved at least five different proteins [2]. The RecQ members belong to the helicase Superfamily II, and as such have the characteristic Rec fold [1].…”
Section: Rationale For Comparison Of MCM and Recq Helicase Familiesmentioning
confidence: 99%
“…The WRN and BLM proteins as well as other members of the RecQ family are characterized by this feature [8]. Both WRN and BLM are involved in DNA repair and a role for WRN in telomere homeostasis in humans is well established [2,9]. MCM2-7 proteins, along with cofactors, are thought to function as the eukaryotic replicative helicase [10].…”
Section: Rationale For Comparison Of MCM and Recq Helicase Familiesmentioning
confidence: 99%